Understanding English grammar : a linguistic introduction - Payne, Thomas Edward, 1951- (Cambridge University Press, 2011)
"Language is primarily a tool for communication, yet many textbooks still treat English grammar as simply a set of rules and facts to be memorised by rote. This new textbook is made for students who are frustrated with this approach and would like instead to understand grammar and how it works. Why are there two future tenses in English? What are auxiliaries and why are they so confusing? Why are English motion verbs hard to use? Why are determiners so important in English? These and many other frequently asked questions are answered in this handy guide. Student learning is supported with numerous exercises, chapter summaries and suggestions for further reading. An accompanying website offers further resources, including additional classroom exercises and a chance to interact with the author. It is the essential grammar toolkit for students of English language and linguistics and future teachers of English as a Second Language"--